2022
DOI: 10.1002/ceat.202100596
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Two‐Fluid Hydrodynamic Model for a Riser Reactor

Abstract: ANSYS Fluent is used to examine the mixing of catalyst zeolite particles with petroleum feedstock and water vapor in a fluid catalytic cracking (FCC) riser. A two-fluid model is developed for tracking catalyst particles and gas mixture in a riser, modeling the granular and gaseous phases as two interpenetrating continua. The hydrodynamic flows are analyzed with the aim to single out the principal physical effects that determine the distribution of particles. The results are compared with a study that is based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 13 publications
3
6
0
Order By: Relevance
“…Much stronger fluidization is achieved by the feedstock injection, which is so intensive that the catalyst fraction decreases to 0.05–0.03 in the upper zones of the reactor. The reported changes in the volume fractions well agree with the results of other numerical studies, e.g., with the results reported by Lee et al Also, as noted in the study by Vorobev et al, these flow fields are solely defined by the hydrodynamic model, and chemistry adds very minor differences to these results.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Much stronger fluidization is achieved by the feedstock injection, which is so intensive that the catalyst fraction decreases to 0.05–0.03 in the upper zones of the reactor. The reported changes in the volume fractions well agree with the results of other numerical studies, e.g., with the results reported by Lee et al Also, as noted in the study by Vorobev et al, these flow fields are solely defined by the hydrodynamic model, and chemistry adds very minor differences to these results.…”
Section: Resultssupporting
confidence: 92%
“…We developed a two-fluid model for tracking of nonisothermal reactive mixing of solid and gas phases in an industrial riser. The work extends our earlier study, 26 in which we reported the results of hydrodynamic modeling of a nonreactive isothermal We conduct nonsteady numerical simulations showing that, if input or operation parameters of the reactor are altered, it takes about 1 min for a new steady-state operation mode to be reached. The major attention in our work is given to the details of the steady-state (normal) operation of the reactor.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations